Establishing the Thematic Structure and Investigating the most Prominent Theta Roles Used in Sindhi Language - Veesar, Z.A.; Kadhim, K.A.; Sriniwass, S. (Australian International Academic Centre, 2015)
This study focuses on the thematic structure of the Sindhi verbs to find theta roles in the Sindhi language. The study tries to answer the research questions; “What are the thematic structures of Sindhi verbs?” and “What are the prominent theta roles in the Sindhi language?” It examines the argument/thematic structure of Sindhi verbs and also finds the theta roles assigned by the Sindhi verbs to their arguments along with the most prominent theta roles used in the Sindhi language. The data come from the two interviews taken from two young native Sindhi speakers, which consist of 2 hours conversation having 1,669 sentences in natural spoken version of the Sindhi language. Towards the end, it has been found that the Sindhi language has certain theta roles which are assigned by the verbs to their arguments in sentences. Each verb phrase in our data is thus examined and studied in detail in terms of Argument/Thematic structure in order to find theta roles in Sindhi language. Thus, in this regard, each verb phrase (in a sentence) has been examined with the help of Carnie’s theoretical framework (Thematic Relation and Theta Roles: 2006) in order to find the prominent theta roles in the Sindhi language. The data have been examined and analysed on the basis of the Carnie’s theoretical framework. The study finds that the Sindhi language has all (09) theta roles which have been proposed by Carnie (2006). It has been found that six prominent theta roles out of nine are used prominently in Sindhi. The six prominent theta roles in Sindhi language are: agent, theme, beneficiary, recipient, locative and goal.